An examination of the temporal order of helping behaviours and emotional exhaustion. (25th July 2020) - Jang, Seulki; Allen, Tammy D.; Kim, Eunsook; Cho, Seonghee
Abstract: An emerging body of research has investigated the relationship between helping (as a type of organizational citizenship behaviour) and emotional exhaustion (as an aspect of employee health). Research has demonstrated a significant relationship between helping and emotional exhaustion, but the theoretical arguments for the causal direction vary across studies. Specifically, some researchers have conceptualized helping as an outcome of emotional exhaustion, while others have regarded helping as a predictor of emotional exhaustion. This lack of theoretical clarity in directionality hinders the field's ability to summarize existing empirical findings cohesively and elucidate theoretical mechanisms. Therefore, this study attempts to clarify the theoretical directionality between helping and emotional exhaustion using four waves of data collected at 6‐month intervals. Autoregressive cross‐lagged analyses with auto‐correlations revealed that more helping was associated with less future emotional exhaustion from Wave 1 to Wave 2, but from Wave 2 to Wave 3, the directionality reversed, as less emotional exhaustion significantly predicted more future helping, and from Wave 3 to Wave 4, both prediction directions were no longer significant. The findings suggest that helping and emotional exhaustion reciprocally affect each other, though the reciprocal pattern may disappear across time. The present study sheds light on the theoretical relationship between helping and emotional exhaustion, and provides theoretical and practical implications.